THE EXPERT ACTIVITY AND NEW STANDARDS OF PROFESSIONAL GLOBALIZATION - Feijoó Gonzalez, Ena Maritza (2015)
In Ecuador, as in many other countries, the application of International Financial Reporting Standards (IFRS) caused controversy not only for accountants, but also for all professionals engaged in the activity as expert advisors of justice. In view of the exposed, it was considered necessary to study the implications of the application of regulations and observe if they generate incidents related to forensic accounting processes. The variables analyzed reflected the lack of preparation of experts to adapt to the new rules.In addition, it has been detected that the correct application of the rules or the adaptation of them to the regulatory framework of expert activities, the actions of the experts could be controlled. Therefore, this paper proposes a general outline for the design of standardized rules, accompanied by a proposal which involves associating the university by inserting expert subjects in the curriculum and activities carried out by experts in the development, design and processing expertise.In the current work a contribution to the accounting expert activity is done by identifying the errors that may occur in the expert development.